Antisurge management of gas pumping units using polyvalent controllers - Семенцов, Георгій Никифорович; Лагойда, Андрій Іванович (Eastern-European Journal of Enterprise Technologies, 2014)
Based on the experimental data, the study of charts of change in productivity of centrifugal supercharger and change in gas pressure ratio, based on which the transfer function of the centrifugal supercharger of gas pumping unit was derived was conducted in the paper. The method of determining the settings of PID and PIDD2 controller through the parameters of the object transfer function is given. Based on the calculated values, simulation of the process with PID, PIDD2, PIDD2D3, PDD2, PDPD controllers was performed in the Matlab software product, and their optimal settings were determined. During the study of the system using polyvalent controllers it was found that the system performance will increase at: PIDD2 controller by 4.44%, PIDD2D3 controller by 22.67%, PDD2 controller by 89.33%, and PDPD controller by 98.22% compared to PID controller.